Gut Microbiome Alterations During HIV/SIV Infection: Implications for HIV Cure - Crakes, Katti R.; Jiang, Guochun (Frontiers in Microbiology, 2019)
Gut mucosal damage associated with Human Immunodeficiency Virus-1 (HIV) infection is characterized by depletion in CD4+ T cells and persistent immune activation as a result of early epithelial barrier disruption and systemic translocation of microbial products. Unique approaches in studying both HIV infection in human patients and Simian Immunodeficiency Virus (SIV) infection in rhesus macaques have provided critical evidence for pathogenesis and treatment of HIV/AIDS. While there is vast resemblance between SIV and HIV infection, the development of gut dysbiosis attributed to HIV infection in chronically infected patients have not been consistently reported in SIV infection in the non-human primate model of AIDS, raising concerns for the translatability of gut microbiome studies in rhesus macaques. This review outlines our current understanding of gut microbial signatures across various stages of HIV versus SIV infection with an emphasis on the impact of microbiome-based therapies in restoring gut mucosal immunity and their translational potential to supplement current HIV cure efforts.